Rediscovery of Chiococca insularis (Ridley) C.M.Taylor & M.R.V. Barbosa (Rubiaceae), a species presumed extinct, on the island of Fernando de Noronha, Pernambuco, Brazil - Maurício Figueira; Bianca Schindler; Jomar G. Jardim; Maria Regina de V. Barbosa (Check List, 2020)
Chiococca insularis (Ridley) C.M.Taylor & M.R.V.Barbosa (Rubiaceae) was described by Henry Nicholas Ridley in 1890, based on a collection he made on the island of Fernando de Noronha (Pernambuco, Brazil) in 1887. Since then, this species had not been collected again and has been treated as probably extinct. After 130 years, we discovered two new populations in the southwestern portion of the island, and the conservation status of the species is reassessed. A full description of the species, with previously unseen or unmeasured characters, habitat information and photographs of the plant and environment are provided.